The detection and discrimination of human body fluids using ATR FT-IR spectroscopy - Orphanou, Charlotte-Maria (Forensic science international, 2015)
•ATR FT-IR spectroscopy can detect blood, saliva, semen and vaginal secretions.•ATR FT-IR can discriminate between the spectra of blood, saliva, semen and vaginal secretions.•ATR FT-IR has demonstrated potential for confirmatory body fluid screening. Blood, saliva, semen and vaginal secretions are the main human body fluids encountered at crime scenes. Currently presumptive tests are routinely utilised to indicate the presence of body fluids, although these are often subject to false positives and limited to particular body fluids. Over the last decade more sensitive and specific body fluid identification methods have been explored, such as mRNA analysis and proteomics, although these are not yet appropriate for routine application. This research investigated the application of ATR FT-IR spectroscopy for the detection and discrimination of human blood, saliva, semen and vaginal secretions. The results demonstrated that ATR FT-IR spectroscopy can detect and distinguish between these body fluids based on the unique spectral pattern, combination of peaks and peak frequencies corresponding to the macromolecule groups common within biological material. Comparisons with known abundant proteins relevant to each body fluid were also analysed to enable specific peaks to be attributed to the relevant protein components, which further reinforced the discrimination and identification of each body fluid. Overall, this preliminary research has demonstrated the potential for ATR FT-IR spectroscopy to be utilised in the routine confirmatory screening of biological evidence due to its quick and robust application within forensic science.